Warunki rozwoju polskiego feminizmu na przełomie XIX i XX wieku - Sikorska–Kowalska, Marta (Instytut Socjologii Uniwersytetu Wrocławskiego, 2019)
The paper focuses on the conditions of activity and programmes of the feminist movement on the Polish territory at the turn of the 20th century. The most important point of the programme of Polish suffragettes back then was to win the right to vote. The Polish Women’s Equal Rights Association (Związek Równouprawnienia Kobiet Polskich) was a radical feminist organization, whose objective was to protect women. Paulina Kuczalska, and her closest colleagues Józefa Bojanowska and Kazimiera Bujwidowa, were all convinced that the so called „women’s question” should definitely be distinguished from other social and political problems. The situation of Polish women before the World War I was similar to the status of women in other countries. The Victorian era had put severe moral obligations on women while allowing men to enjoy a far wider scope of rights. This is why the call for the „rights for women and purity for men” was to be found among Polish sufragettes’ slogans. Polish women had no voting rights which was also the case in most of the European countries. Moreover, they had restricted access to education, limited civil rights and they experienced imparity in social and family life. All aspects of the women’s problematic situations were present in programmes of those Polish suffragettes as they took advantage of the opportunity provided by the independence of Poland eventually winning the right to vote.
Keywords: history of women; History of Poland; feminism